Checklist of the water mites (Acari: Hydrachnidia) of Turkey: First supplement - Erman, Orhan; Gulle, Pinar; Ozkan, Muhlis; Candogan, Hulya; Boyaci, Yunus Omer (Magnolia Press, 2019)
As a first supplement to the list of the water mites (Acari, Hydrachnidia) fauna of Turkey compiled by Erman et al. (2010), a faunistic list of water mites from Turkey is presented based on published data after 2010. Including the new data, the total number of taxa recorded from Turkey reaches 335 species, in 62 genera and 25 families. The new synonym is established Trichothyas (Lundbladia) anatolica Boyaci & Gulle, 2014 = Dacothyas kandilliensis Oezkan & Bader, 1988. Furthermore, for each family, the number of species is given, both, for this study and totally.
Keywords: Water mites; new species; biodiversity; taxonomy; Turkey